2010
DOI: 10.3758/cabn.10.2.316
|View full text |Cite
|
Sign up to set email alerts
|

Event-related brain potentials and cognitive processes related to perceptual—motor information transmission

Abstract: In the present study, event-related potentials (ERPs) were recorded to investigate cognitive processes related to the partial transmission of information from stimulus recognition to response preparation. Participants classified two-dimensional visual stimuli with dimensions size and form. One feature combination was designated as the go-target, whereas the other three feature combinations served as no-go distractors. Size discriminability was manipulated across three experimental conditions. N2c and P3a ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 50 publications
(69 reference statements)
2
10
1
Order By: Relevance
“…Electrophysiological studies by Potts and Tucker (2001), but see also Kopp and Wessel, 2010;O'Donnell et al, 1997;Potts, 2004;Potts et al, 1996) showed that the posterior N2 is accompanied by a frontal positivity named P2. The so called P2/N2 complex is assumed to reflect target detection processes based on the interaction between (1) a perceptual system coding the physical features of the stimulus (i.e.…”
Section: Introductionmentioning
confidence: 96%
“…Electrophysiological studies by Potts and Tucker (2001), but see also Kopp and Wessel, 2010;O'Donnell et al, 1997;Potts, 2004;Potts et al, 1996) showed that the posterior N2 is accompanied by a frontal positivity named P2. The so called P2/N2 complex is assumed to reflect target detection processes based on the interaction between (1) a perceptual system coding the physical features of the stimulus (i.e.…”
Section: Introductionmentioning
confidence: 96%
“…As reported by Johnstone et al(2010), the N2b amplitude in a Running head: Energetic factors in impulsivity 6 flanker task appeared to be sensitive to stimulus degradation and therefore to the increasing difficulty of visual discriminability. The N2c is thought to reflect the inhibition or suppression of the automatically, but erroneously primed responses (Gehring et al, 1992;Kopp et al, 1996), or more generally, the process of response conflict monitoring (Folstein and Van Petten, 2008;Kopp and Wessel, 2010;Yeung et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to the N2, the P3 occurring at 250-700 ms after stimulus onset is also related to inhibitory control processes Johnstone et al, 2010;Kopp and Wessel, 2010). The peak latency of P3 is considered as a measure of stimulus evaluation time (Polich, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The latter component is considered semiautomatic, in that it is elicited by oddball stimuli regardless of task relevance [5], [6]. The N2c, which commonly precedes the P3b component, is associated with classification tasks [13].…”
Section: Introductionmentioning
confidence: 99%